A case study: Examining strength and physiological variable changes over an ECP training year - Phillips, M. B.; Barfield, A. J.-P.; Lockert, A. (Journal of Sport and Human Performance, 2016)
Objective: To document change in performance and hormone levels over the course of a one year training cycle in a professional CrossFit® athlete. The current study is the first to document changes resulting from a one-year training cycle in an extreme conditioning program.